Emergency Angioembolization for Life-Threatening Haemorrhage in Wilms Tumour - Areej Salim; Sajid Ali; Muhammad Ali Sheikh; Tariq Latif; Islah Ud Din (Journal of Cancer and Allied Specialties, 2023)
Introduction: Renal artery embolization has been used in a palliative fashion for symptomatic relief of hematuria or flank pain in unresectable renal cell carcinoma in adults. There is limited data on using embolization for actively bleeding and unresectable tumours in the oncological pediatric population. Case description: A previously healthy, five-year-old boy with no significant past medical or surgical history presented to the clinic with gradually worsening abdominal distension associated with occasional abdominal pain, gross hematuria, and lethargy for four months. Diagnostic investigations showed an 18 cm left-sided metastatic (pulmonary) renal tumour (Wilms), which was deemed unresectable on imaging. Treatment was planned on SIOP-RTSG protocol. However, he became hemodynamically and vitally unstable with acute sudden distension of the abdomen on the left side after the first cycle of chemotherapy. Imaging showed active bleeding from an inferior branch of the left renal artery. Selective angioembolization was done, and chemotherapy was reinitiated with a patent left main renal artery. Following the fourth cycle of chemotherapy, he developed hemodynamic instability and abdominal pain; imaging revealed the resolution of pulmonary nodules and bleeding from the left renal artery (main); this was again embolized, and the patient was stabilized. The patient was operated on after optimization and complete resection of the mass was done with negative margins. On six months follow up, he is well. Practical implications: To the best of our knowledge, this is the first case where angioembolization has been done in conjunction with neoadjuvant chemotherapy to downsize a Wilms Tumor to achieve favourable outcomes. Continued research efforts are necessary to optimize strategies and improve the prognosis for pediatric patients, and this case is one of the prime examples.